Reactive-pragmatic activism: The trend and pattern of Indonesia’s Generation Z digital movement - Cep Deni Muchlis; A. Bakir Ihsan; Mohammad Hasan Ansori; Ismail Suardi Wekke (SIMULACRA: JURNAL SOSIOLOGI, 2026)
This study aims to explore the manner in which Generation Z (Gen Z) engages with socio-political activities in the digital sphere, where the swift dissemination of information influences the nature and intensity of collective actions. The findings indicate that Gen Z's responses to socio-political issues are generally expressed in two paradoxical mainstreams: apolitical tendencies (political alienation) and political tendencies (political activism), each of which exhibiting distinct variations. To examine this phenomenon, the study mainly employs a semi-systematic literature review (semi-SLR), analyzing 40 curated articles from an initial pool of 200 Scopus-indexed publications (2020–2025). The selection process adhered to a rigorous semi PRISMA-based framework. The methodological analysis reveals that Gen Z's engagement with socio- political phenomena tends to intensify as these issues predominantly gain attention on social media (the digital realm). However, this intensification has not consistently resulted in substantive political change. Indeed, at a certain juncture, Gen Z movements remain in what Dahrendorf termed as the "quasi- group" phase, which potentially evolves into a highly responsive collective action when triggered by pragmatic and significant issues. This phenomenon is referred to as a reactive-pragmatic activism, a form of activism motivated by the pursuit of immediate results without an ideological foundation.